2018
DOI: 10.1002/pssa.201800488
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Investigation of Non‐Isothermal Decomposition of Pt Acetylacetonate as One‐Step Size‐Controlled Synthesis of Pt Nanoparticles

Abstract: Interest in the development of state-of-the-art methods for synthesis of Pt nanoparticles is dictated by both unique properties of platinum itself and the wide range of platinum nanoparticles applications. Platinum acetylacetonate and platinum nanoparticles produced by the thermal decomposition of Pt(acac) 2 are studied via in situ X-ray diffraction and Raman spectroscopy, thermal gravimetry, scanning (SEM), and transmission electronic microscopy (TEM). The experiments are made at heating rates of 1 and 5 K mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…38 The second weight loss observed between 150 and 250 °C was attributed to the thermal decomposition of Pt(acac) 2 and Mo(CO) 6 . 39,40 In this step, Pt metal seeds were formed by reducing the power of CO gas, which was derived from the decomposition of Mo(CO) 6 . The XPS analysis revealed that the metallic Mo peak, located at 228.3 eV, was not detected in the Mo 3d spectrum of PtMo/ C-200 (Figure 2c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The second weight loss observed between 150 and 250 °C was attributed to the thermal decomposition of Pt(acac) 2 and Mo(CO) 6 . 39,40 In this step, Pt metal seeds were formed by reducing the power of CO gas, which was derived from the decomposition of Mo(CO) 6 . The XPS analysis revealed that the metallic Mo peak, located at 228.3 eV, was not detected in the Mo 3d spectrum of PtMo/ C-200 (Figure 2c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The first weight loss observed at approximately 100 °C results from the vaporization of residual H 2 O in the powder samples . The second weight loss observed between 150 and 250 °C was attributed to the thermal decomposition of Pt(acac) 2 and Mo(CO) 6 . , In this step, Pt metal seeds were formed by reducing the power of CO gas, which was derived from the decomposition of Mo(CO) 6 . Mo false( CO false) 6 false( normalg false) Mo false( CO false) 6 false( ads false) Mo false( ads false) + 6 CO false( normalg false) …”
Section: Resultsmentioning
confidence: 99%
“…Mostly, organometallic precursors have been used for the preparation of bimetallic nanoalloy particles [50][51][52]. To the best of our knowledge, only a few reports are available on the preparation of PtNPs and AgNPs using platinum (II) acetylacetonate (Pt(acac) 2 ) [53][54][55] and silver (I) acetylacetonate (Ag(acac)) [44,56] as precursors, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Since the capacitance of oxide-based composites strongly depends on their microstructural characteristics that may differ at various synthesis conditions and component ratios, the development of an efficient and simple synthesis method that would ensure the production of composite electrode materials with optimal specific electrochemical properties is a relevant task. Furthermore, it was previously shown [ 22 , 23 ] that non-isothermal decomposition of Pt acetyl acetonate enables access to Pt/C nanoparticles whose surface area can reach 100 m 2 /g. This synthesis method is very simple and requires only two stages; moreover, no washing, filtering or subsequent drying of a specimen are required.…”
Section: Introductionmentioning
confidence: 99%